Green Economy Dan Tanggung Jawab Moral Manusia Terhadap Lingkungan Dalam Perspektif Islam - Bunga Andini; Mohd Winario; Rifqil Khairi (Multidisciplinary Journal of Religion and Social Sciences, 2026)
The concept of green economy has developed as a development paradigm that emphasizes the balance between economic growth, environmental sustainability, and social justice amidst the global ecological crisis. From an Islamic perspective, green economy is not merely a technical approach, but also a manifestation of human moral and spiritual responsibility as caliphs on earth. Humans are required to maintain balance (mīzān), avoid damage (fasād), and ensure the sustainability of resources for future generations. This study aims to analyze the relationship between the principles of green economy and human moral responsibility within the framework of Islamic values, by integrating the Qur'an, Hadith, and maqāṣid al-sharī‘ah. The method used is a qualitative literature study from classical and contemporary sources related to Islamic economics and environmental ethics. The results of the study indicate that green economy principles such as resource efficiency, emission reduction, distributive justice, and ecosystem sustainability are in line with Islamic values, especially amanah (trust), justice (‘adl), benefit (maṣlaḥah), and the prohibition of isrāf and tabdhīr. This responsibility is both individual and collective, involving the state, economic actors, and society in realizing sustainable development.